Peran E-commerce bagi Islamic Fashionpreneur Menuju Society Digital Di Era Pandemi Covid-19 - Indriya Indriya; Farhan Zamzamy; Annisa Yasrien Algaisya; Dinda Rosaliana; Nurul Tari Rahmawati (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
This article aims to discuss Islamic Fashionpreneurs (MSMEs) in adjusting to market their products in the digital era. In accordance with the direction of the Indonesian government, the E-commerce literacy MSME development scheme in the digital era is an alternative that saves business actors, especially in the midst of the Covid-19 pandemic. Every Islamic fashionpreneur (MSME) must be ready to face this cultural shift, where the fulfillment of needs must go hand in hand with technological developments. The research method using qualitative begins with data collection through observation, field surveys by presenting questionnaires, interviews. The results obtained from this study are; First, Islamic Fashionpreneurs (MSMEs) must be able to adapt to advances in digital technology (E-commerce), which has a significant influence on sales. Second, to support the acceleration of digital transformation, Islamic Fashionpreneurs (MSMEs) must be active and synergize with various parties, including the government, academics, communities and practitioners themselves. Third, there is digital literacy education through consistent training and assistance for Islamic Fashionpreneur MSME business actors from the government, academia, and the community.Keywords: E-Commerce; Islamic Fashion; Entrepreneur (UMKM); Digital Society; Covid-19 Pandemic Abstrak Artikel ini bertujuan untuk membahas mengenai Islamic Fashionpreneur (UMKM) dalam menyesuaikan memasarkan produknya di era digital. Sesuai dengan arahan pemerintah Indonesia, skema pengembangan UMKM melek E-commerce di era digital menjadi alternatif yang menyelamatkan pelaku usaha, terlebih di tengah pandemi Covid-19. Setiap Islamic fashionpreneur (UMKM) harus siap menghadapi pergeseran budaya ini, dimana pemenuhan kebutuhan harus beriringan dengan perkembangan teknologi. Metode penelitian menggunakan kualitatif diawali pengumpulan data melalui pengamatan, survei lapangan dengan menyajikan kuesioner, wawancara. Hasil yang didapatkan dari penelitian ini adalah; pertama, pelaku Islamic Fashionpreneur (UMKM) harus dapat beradaptasi dengan kemajuan teknologi digital (E-commerce), yang memiliki pengaruh signifikan terhadap penjualan. Kedua, untuk mendukung percepatan transformasi digital para pelaku Islamic Fashionpreneur (UMKM), harus aktif dan bersinergi dengan berbagai pihak baik pemerintah, akademisi, komunitas dan praktisi itu sendiri. Ketiga, adanya Edukasi literasi digital melalui pelatihan dan pendampingan secara konsisten bagi para pelaku usaha Islamic Fashionpreneur UMKM baik dari pemerintah, akademisi, serta komunitas.Kata Kunci : E-Commerce, Islamic Fashion, Entrepreneur (UMKM), Society digital, Pandemi Covid-19